Almond Shell Based Activated Carbon Prepared Via Microwave Irradiated For Chloramphenicol Removal - Saw, Wen Yi (Universiti Sains Malaysia, 2021)
In this study, low cost and efficient activated carbon (AC) was prepared from almond shell (AS) through microwave irradiation technique for chloramphenicol (CAP) removal. The optimization of almond shell based activated carbon (ASAC) preparation conditions of microwave irradiation power and radiation time for CAP adsorption was done by using Response Surface Methodology (RSM). The optimum preparation conditions determined were at radiation power and time of 490 W and 6 minutes, respectively, which resulted in 96.23% of CAP removal and 41.53% of ASAC yield. The optimized ASAC was characterised through Brunauer–Emmett–Teller (BET) surface area and pore structural analysis, proximate and elemental analysis, scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FTIR). For batch adsorption study, various operational parameters such as initial concentration, contact time, solution temperature and pH on CAP adsorption were investigated. The experimental data were analyzed using three adsorption isotherm models: Langmuir, Freundlich and Temkin. It was found that the adsorption was best fitted with the Langmuir isotherm model, with maximum CAP adsorption capacity at 63.29 mg/g. Kinetic studies for CAP adsorption indicated that the adsorption process followed a pseudo second order (PSO) kinetic model. The thermodynamic parameters such as standard Gibbs free energy (∆